A 2D MTF approach to evaluate and guide dynamic imaging developments - Chao, Tzu-Cheng; Chung, Hsiao-Wen; Hoge, W. Scott; Madore, Bruno (Magnetic resonance in medicine, 2010)
As the number and complexity of partially sampled dynamic imaging methods continue to increase, reliable strategies to evaluate performance may prove most useful. In the present work, an analytical framework to evaluate given reconstruction methods is presented. A perturbation algorithm allows the proposed evaluation scheme to perform robustly without requiring knowledge about the inner workings of the method being evaluated. A main output of the evaluation process consists of a two‐dimensional modulation transfer function, an easy‐to‐interpret visual rendering of a method's ability to capture all combinations of spatial and temporal frequencies. Approaches to evaluate noise properties and artifact content at all spatial and temporal frequencies are also proposed. One fully sampled phantom and three fully sampled cardiac cine datasets were subsampled (R = 4 and 8) and reconstructed with the different methods tested here. A hybrid method, which combines the main advantageous features observed in our assessments, was proposed and tested in a cardiac cine application, with acceleration factors of 3.5 and 6.3 (skip factors of 4 and 8, respectively). This approach combines features from methods such as k‐t sensitivity encoding, unaliasing by Fourier encoding the overlaps in the temporal dimension‐sensitivity encoding, generalized autocalibrating partially parallel acquisition, sensitivity profiles from an array of coils for encoding and reconstruction in parallel, self, hybrid referencing with unaliasing by Fourier encoding the overlaps in the temporal dimension and generalized autocalibrating partially parallel acquisition, and generalized autocalibrating partially parallel acquisition–enhanced sensitivity maps for sensitivity encoding reconstructions. Magn Reson Med, 2010. © 2009 Wiley‐Liss, Inc.